British Unions: A Cultural Analysis - Balfour, W. Campbell (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1958)
SummaryTrade unions in Britain have developed against a particular cultural background, and many of their attitudes and aims stem from this environment and its effect on their members. The last twenty or thirty years have seen great changes in political, social and economic backgrounds: this has led to certain strains and tensions in the union structure, and to the gradual abandonment of traditional symbols, beliefs and modes of action.